Grit and its associated factors among final year pharmacy students in public universities in Nigeria: A cross-sectional study - Isah, Abdulmuminu; Nwachuya, Chukwuemeka Augustine; Aniefuna, Chisom Victoria; Onyehalu, Jennifer Chinaecherem; Mmuo, Somadina Sixtus; Agozue, Onyinyechi Cynthia; Ugwu, Dickson Onyedikachi; Amandi, Nancy Chinwe; Asogwa, John Chidimma; Umeh, Anthony Uche; Ugochukwu, Ezinwanne Jane; Ubaka, Chukwuemeka Micheal (Pharmacy Education, 2023)
Background: Assessing grit among pharmacy students provides insights into the students' experiences as well as the importance of implementing interventions to increase their levels of grit. The purpose of this study was to assess students' grit in Nigerian pharmacy schools and to identify factors that predict the amount of grit among pharmacy students. Methods: This study utilised a nine-item questionnaire-based cross-sectional design among final-year pharmacy students from one public university, in each of the six geopolitical zones of Nigeria for a month. Descriptive and inferential statistics were employed. Results: A total of 590 pharmacy students responded to the questionnaire (response rate = 66.89%). Most students 409 (69.32%) were between the ages of 20 - 25 years. A majority, 573 (97.1%) reported being free from any chronic diseases and 427 (72.37%) reported being engaged in extracurricular activities. A group mean grit score of 37.091 ± 0.253 was observed. Students from all the schools reported ‘Not Like me’ 14 (2.37%) to ‘I have overcome setbacks to conquer an important challenge’, while 275 (46.61%) chose ‘Very much like me’. Predictors of high grit level were institution (Beta, p-value), mode of accommodation (ꞵ = 1.494, p = .039), and sponsorship (ꞵ = 4.207, p = .047). Conclusion: Pharmacy students in Nigeria have a high grit level and the institution of study had an impact on the level of grit.